One-pot system for synthesis, assembly, and display of functional single-span membrane proteins on oil–water interfaces - Yunker, Peter J. (Proc Natl Acad Sci U S A, 2016)
Single-span membrane proteins (ssMPs) represent approximately one-half of all membrane proteins and play important roles in cellular communications. However, like all membrane proteins, ssMPs are prone to misfolding and aggregation because of the hydrophobicity of transmembrane helices, making them difficult to study using common aqueous solution-based approaches. Detergents and membrane mimetics can solubilize membrane proteins but do not always result in proper folding and functionality. Here, we use cell-free protein synthesis in the presence of oil drops to create a one-pot system for the synthesis, assembly, and display of functional ssMPs. Our studies suggest that oil drops prevent aggregation of some in vitro-synthesized ssMPs by allowing these ssMPs to localize on oil surfaces. We speculate that oil drops may provide a hydrophobic interior for cotranslational insertion of the transmembrane helices and a fluidic surface for proper assembly and display of the ectodomains. These functionalized oil drop surfaces could mimic cell surfaces and allow ssMPs to interact with cell surface receptors under an environment closest to cell–cell communication. Using this approach, we showed that apoptosis-inducing human transmembrane proteins, FasL and TRAIL, synthesized and displayed on oil drops induce apoptosis of cultured tumor cells. In addition, we take advantage of hydrophobic interactions of transmembrane helices to manipulate the assembly of ssMPs and create artificial clusters on oil drop surfaces. Thus, by coupling protein synthesis with self-assembly at the water–oil interface, we create a platform that can use recombinant ssMPs to communicate with cells.